2018
DOI: 10.1002/2018jb015527
|View full text |Cite
|
Sign up to set email alerts
|

Noise Characteristics of High‐Rate Multi‐GNSS for Subdaily Crustal Deformation Monitoring

Abstract: High‐rate GPS (Global Positioning System) has the potential to record crustal motions on a wide subdaily timescale from seconds to hours but usually fails to capture subtle deformations which are often overwhelmed by the centimeter noise of epoch‐wise GPS displacements. We hence investigated high‐rate multi‐GNSS (Global Navigation Satellite System) by processing 1 Hz GPS/GLONASS/BeiDou data at 15 static stations over 24 days and also those from the 8 August 2017 Jiuzhaigou Mw 6.5 earthquake. In contrast to hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 41 publications
3
35
0
Order By: Relevance
“…In their studies, the seven-day model or other multiple-day models had lower noise levels than the single-day model, and hence the former outperformed the latter in variance reduction. Geng et al [30] also reported that the multiple-day model was better than the single-day model. It is because their PPP derived residuals possibly included orbit error and troposphere delay, which contaminated the multipath correction models.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In their studies, the seven-day model or other multiple-day models had lower noise levels than the single-day model, and hence the former outperformed the latter in variance reduction. Geng et al [30] also reported that the multiple-day model was better than the single-day model. It is because their PPP derived residuals possibly included orbit error and troposphere delay, which contaminated the multipath correction models.…”
Section: Discussionmentioning
confidence: 97%
“…Hence, this type of receiver has wide applications, including attitude determination, ground-based carrier phase wind-up calibration, and phase center variation correction [28,31]. Using such single-differenced observable residuals, we are able to isolate the multipath errors much thoroughly, and to avoid ad-hoc 'zero-mean' assumption [25,26] and un-modeled errors from un-differenced observable residuals [29,30]. Thus the assessment of ASF is more accurate and objective.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, high-rate GNSS is tumbled by its several orders of magnitude higher noise than that of conventional inertial seismograph, especially in case of very strong dynamic stress of up to 2 g or even more (e.g., Geng et al, 2017Geng et al, , 2018. Based on a GPS signal simulator, Ebinuma and Kato (2012) found that the Trimble NetR8 receiver's recordings for a 5-Hz sinusoidal signal suffered harshly a 125% amplitude error and RESEARCH LETTER 10.1029/2020GL087161 Key Points: • A new GNSS receiver architecture is developed by embedding both accelerometer and gyroscope to capture fierce seismic displacements • GNSS displacement error and phase lag are both reduced by 70% and 85% to 2 mm and 8.0 ms, respectively, compared to conventional receivers • Six-degree-of-freedom seismogeodesy is achieved with the displacement error and phase lag reduced further to 0.9 mm and 3.5 ms, respectively 10.1029/2020GL087161 a 74 • (or 40 ms, milliseconds) phase lag in case of an acceleration as high as 2 g. In a shake table experiment instead, Wang et al (2012) also told that the Trimble NetRS receiver's displacement measurements were likely to overshoot in amplitude by about 2 cm or almost 100% in contrast to the benchmark displacements, whenever the acceleration was over 1 g. While such amplitude errors and phase lags were observed frequently with regard to Trimble equipments struck by great accelerations and jerks, Ebinuma and Kato (2012) and Berglund et al (2015) illustrated that many mainstream GNSS receivers (e.g., Septentrio, Javad and Topcon) could also experience similar problems under extreme dynamic stress.…”
Section: Introductionmentioning
confidence: 99%